Formation and characteristics of glucose oligomers during the hydrolysis of cellulose in hot-compressed water - Yu, Yun (Curtin University, 2009)
Energy production from fossil fuels results in significant carbon dioxide emission, which is a key contributor to global warming and the problems related to climate change. Biomass is recognized as an important part of any strategy to address the environmental issues related to fossil fuels usage for sustainable development. The carbohydrates in lignocellulosic biomass mainly exist as cellulose and hemicellulose. These materials must be broken down through hydrolysis for the production of desired biomass extracts (e.g. sugar products), which can then be converted into ethanol. Developing efficient hydrolysis processes is essential to producing biomass extracts of desired properties. Due to its unique physical and chemical properties, hot compressed water (HCW) may be utilized as both solvent and reactant simultaneously in various applications including hydrolysis. So far, there has been a lack of fundamental understanding of biomass and cellulose hydrolysis in HCW. The present study aims to characterize the formation of glucose oligomers in the primary liquid products, and to bring some new insights into the reaction mechanisms of cellulose hydrolysis in HCW.The specific objectives of this research include the development of a new sampling and analytical method to characterise the glucose oligomers in the liquid products, to investigate the formation of precipitate from fresh liquid products, to understand the primary reactions on the surface of reacting cellulose particle during hydrolysis in HCW at various temperatures, to study the significant differences in hydrolysis behavior of amorphous and crystalline portions within microcrystalline cellulose, to investigate the evolution of primary liquid products with conversion, and to study the effect of ball milling on the hydrolysis of microcrystalline cellulose in HCW. To accomplish these objectives, a semicontinuous reactor system was developed and set up to carry out the experiments of the hydrolysis of various cellulose samples in HCW. The liquid samples were characterised by a number of analytical instruments, including the introduction of a new technique to analyse the glucose oligomers in the liquid sample.First of all, this study shows the presence of a wide range of glucose oligomers with the degree of polymerizations (DPs) up to 30 and their derivatives in the fresh liquid products, which is produced from cellulose hydrolysis in HCW using a semicontinuous reactor system at 280 °C and 20 MPa, by a high performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD). None of those oligomers can be detected by a high performance liquid chromatography with evaporative light scattering detector (HPLC-ELSD) that however can detect glucose oligomers with DPs up to 6 after the liquid solutions are concentrated by 25 times via vacuum evaporation at 40 °C, during which a large amount of precipitate was formed. While quantitative analysis of the glucose oligomers with DPs > 5 cannot be done due to the lack of standards, that of the glucose oligomers from glucose (DP = 1) to cellopentaose (DP = 5) using both HPAEC-PAD and HPLC-ELSD are in good agreement, suggesting that these low- DP glucose oligomers do not contribute to the precipitate formation.Secondly, the study of a set of purposely-designed precipitation experiments indicates that the precipitation starts as the fresh liquid sample is collected and is fast during the initial 8 hours, levels off as the precipitation time increases further and completes after 120 hours (5 days). Based on a new approach developed for the quantification of glucose oligomers retention during the precipitation process, it is found that the contribution of glucose oligomers to precipitate formation increases with DP. The higher the DP is, the lower the solubility of the glucose oligomer is. The glucose oligomers from glucose to cellopentaose and their derivatives (DPs = 1- 5) contribute little to the precipitate formation, which explains why HPLC-ELSD can correctly analyze these glucose oligomers in the concentrated solutions prepared by vacuum evaporation. The glucose oligomers and their derivatives with DPs > 5, which are soluble in HCW but become supersaturated in the solutions under ambient conditions, are responsible for precipitate formation. Most (but not all) of the glucose oligomers and their derivatives with DPs > 16 contribute to the precipitate formation as tiny peaks of these glucose oligomers are still shown in the chromatograms, suggesting that these glucose oligomers have very low (but non-zero) solubilities in ambient water. The retentions of glucose oligomers and their derivatives increase substantially with the DP decreasing from 16 to 6, indicating that less of these lower-DP oligomers contribute to the precipitate formation. To avoid the effect of precipitation on oligomer analysis, the fresh liquid products must be analyzed immediately after sample collection.Thirdly, this study reports the experimental results on the primary liquid products from the hydrolysis of microcrystalline cellulose in HCW at 10 MPa and 230-270 °C using a semicontinuous reactor system under optimised reaction conditions. The primary liquid products contain glucose oligomers and their derivatives with a wide range of degrees of polymerization (DPs) from 1 to a maximal DP, which increases with temperature from 23 at 230 °C, to 25 at 250 °C then to 28 at 270 °C. Temperature also has a significant influence on the distribution of glucose oligomers in the primary liquid products. The results suggest that the hydrolysis reactions proceed on the surface of reacting cellulose particles via the cleavage of the accessible glycosidic bonds within the structure of microcrystalline cellulose in a manner with randomness. Thermal cleavage of glycosidic bonds seems also to occur on the accessible surface of the reacting cellulose particles in a similar manner. The randomness of these reactions seems to be temperature dependent and is likely related to the change in the accessibility of glycosidic bonds as results of the cleavage of hydrogen bonds in the structure of microcrystalline cellulose. The hydrolysis reactions seem also to be accompanied by other parallel reactions (e.g. cross-linking reactions), which may affect the primary liquid products as well, particularly at high temperatures. The post hydrolysis of primary liquid products has a high glucose yield of ~80% on a carbon basis, suggesting that combining HCW and enzymatic hydrolysis may be a promising technology for sugar recovery from lignocellulosic feedstocks.Fourthly, this study finds that the reactivity of microcrystalline cellulose exhibits a considerable reduction in the initial stage during hydrolysis in HCW, due to the presence of amorphous structure in microcrystalline cellulose. Further analysis of the liquid products obtained at various temperatures suggests that amorphous portion within microcrystalline cellulose contains some short glucose chain segments hinged with crystalline cellulose via weak bonds (e.g. hydrogen bonds). These short chain segments are reactive components responsible for the formation of C4-C13 in the primary liquid products during hydrolysis in HCW at temperatures as low as 100 °C. The minimal temperature for breaking the glycosidic bonds in those short chain segments to form glucose monomer from amorphous portion within microcrystalline cellulose is ~150 °C. However, the minimal temperature at which glucose monomer starts to be produced from the crystalline portion within microcrystalline cellulose is around 180 °C, apparently due to the limited accessibility of the glycosidic bonds in the crystalline portion to HCW as results of the strong intra- and inter-molecule hydrogen bonding networks. The differences of chain length and hydrogen bonding pattern between amorphous and crystalline cellulose also greatly affects the distribution of glucose oligomers in their liquid products during hydrolysis in HCW. Generally, amorphous cellulose produces more glucose mono- and oligomers at the same hydrolysis temperature, but the selectivity ratios of glucose oligomers in the primary liquid products from amorphous and crystalline portions do not show a monotonic trend with DP, at least partly resulting from the presence of shorter glucose chain segments in amorphous portion within the microcrystalline cellulose.Fifthly, this study demonstrates the dynamic evolution of the specific reactivity and primary liquid products with conversion during the hydrolysis of both amorphous and crystalline cellulose in HCW. The results suggest the dynamic changes in cellulose structure occur during conversion, and strongly depend on reaction temperature. Results from a set of purposely-designed two-step experiments further confirm at least two mechanisms which may be responsible for such structural changes. One is the selective consumption of the reactive components within the intrinsically heterogeneous cellulose at early conversions. This mechanism dominates during the hydrolysis of at low temperatures, e.g. 180-200 °C for amorphous cellulose and 230 °C for microcrystalline cellulose. The other is the combined effects of various parallel reactions during hydrolysis in HCW, including cleavage of hydrogen bonds, degradation reactions and cross-linking reactions. Enhanced hydrogen bond cleavage increases the production of glucose oligomers. However, parallel degradation reactions and cross-linking reactions decrease the selectivities of glucose oligomers. The effect of cross-linking increases significantly with temperature and becomes dominant at high temperature, leading to a structural condensation hence a reduction in the specific reactivity of cellulose and the selectivities of glucose oligomers in the primary liquid products.Sixthly, this study investigates the effect of ball milling as a pretreatment method on microcrystalline cellulose hydrolysis in HCW. Ball milling leads to a considerable reduction in cellulose particle size and crystallinity therefore a significant increase in the specific reactivity during hydrolysis in HCW. It is found that crystallinity is the dominant factor in determining the hydrolysis reactivity of cellulose in HCW while particle size only plays a minor role. Ball milling also significantly influences the distribution of glucose oligomers in the primary liquid products of hydrolysis. Ball milling increases the selectivities of glucose oligomers at low conversions. At high conversions, the reduction in chain length plays an important role in glucose oligomer formation since cellulose samples become more crystalline. An extensive ball milling completely converts the crystalline cellulose into amorphous cellulose, leading to a significant increase in the formation of high-DP glucose oligomers. It seems that ball milling is a good strategy for improving cellulose hydrolysis reactivity in HCW.Overall, the present research has provided valuable information for the fundamental understanding of the mechanisms of cellulose hydrolysis in HCW. The development of a sampling and analytical method makes it possible to characterise the glucose oligomers in the liquid products and understand the formation of precipitate in the liquid products. The primary liquid products of cellulose hydrolysis in HCW, which were firstly reported in this field, are of great importance to elucidate the primary hydrolysis reactions of cellulose hydrolysis in HCW. The structural differences between amorphous and crystalline cellulose, as well as the evolution of structural changes with conversion during hydrolysis in HCW were also revealed. This study further estimated the effect of ball milling on the improvement in the performance of cellulose hydrolysis in HCW.